Teori Hukum Penitensier Terhadap Pelaku Kekerasan Seksual Terhadap Anak - Syakinah Hamid Alamri; Lisnawaty W Badu; Avelia Rahmah Y. Mantali (Hukum Inovatif : Jurnal Ilmu Hukum Sosial dan Humaniora, 2024)
Children have human rights, just like adults have, to protect children's rights, not many parties think about it and take concrete steps. Likewise, efforts to protect children's rights are violated by the State, adults, their own environment or their parents who do not really pay attention to the interests of the child's future. Child protection is not only attached to the individual child, but also to other humans. This is a consequence of humans as social creatures who cannot be separated from other humans. Criminal law then exists to regulate various acts that violate human rights which are then punished. Of course, criminal law cannot be implemented properly if there is no other legal knowledge that accompanies it, including penitentiary law which is known as Penal Law or legal science that studies punishment. The Penitentiary Law is not a legal rule that can immediately punish criminals arbitrarily, but requires human rights to be taken into account. This article focuses on whether penitentiary laws violate human rights or not. The purpose of this paper is to examine in more depth the effectiveness of penitentiary laws in sanctioning sexual crime perpetrators and protecting sexual crime victims. The research method used is normative law with library research techniques analyzed qualitatively using a statutory approach and a conceptual approach. The results of the research conclude that the Penitentiary Law is a regulation that seeks to continue to fight for the human rights of people who have been violated by the perpetrator of a crime by punishing them, but the model of punishment given still pays attention to the human rights of the perpetrator of the crime being punished.